2020
DOI: 10.1016/j.jvsv.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Humanitas COVID-19 Task Force Venous and Arterial Thromboembolic Complications in COVID-19 Patients Admitted to an Academic Hospital in Milan, Italy

Abstract: ence to, the wearing of elastic compression stockings by patients with chronic venous insufficiency (CVI), including knowledge and awareness of the need and their efficacy and patient discomfort.Study Summary: This qualitative study assessed 10 patients with CVI who were undergoing elective surgical intervention. Focused semistructured face-to-face interviews were performed by experienced qualitative researchers with patients chosen because of their noncompliance with graduated compression stockings (CS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 0 publications
6
66
1
2
Order By: Relevance
“…Symptomatic VTE was detected in 21 out of 75 (28%) ICU patients and 4 out of 123 (3.3%) ward patients (sub-distribution hazard ratios 3.9; 95% CI 1.3-12) [99]. Lodigiani et al [100] studied venous and arterial thromboembolic complications in 388 hospitalized patients. Thromboprophylaxis was used in all ICU patients and 75% of those on the general ward.…”
Section: Coagulation Abnormalities Dic and Thromboembolismmentioning
confidence: 99%
“…Symptomatic VTE was detected in 21 out of 75 (28%) ICU patients and 4 out of 123 (3.3%) ward patients (sub-distribution hazard ratios 3.9; 95% CI 1.3-12) [99]. Lodigiani et al [100] studied venous and arterial thromboembolic complications in 388 hospitalized patients. Thromboprophylaxis was used in all ICU patients and 75% of those on the general ward.…”
Section: Coagulation Abnormalities Dic and Thromboembolismmentioning
confidence: 99%
“…Patients were admitted to a university hospital (Humanitas Clinical and Research Hospital, Rozzano, Milan, Italy) from February to April 2020. 7 For this analysis, we focused only on the temporal course of D-dimer and CRP, as these biomarkers were most frequently used for patient monitoring after early descriptions of their potential prognostic value in COVID-19. 4 We refrained from analysis of venous thromboembolic (VTE) events, because this topic has been extensively addressed 7,8 and because D-dimer levels often guided VTE imaging, which might have led to erroneous risk estimates.…”
mentioning
confidence: 99%
“…2 Patients hospitalized for COVID-19, especially those requiring intensive care, are increasingly recognized to be at higher risk for VTE. 3 The WHO, 4 the American NIH, 5 and International Society on Thrombosis and Haemostasis, 6 among other societies, 7,8 recognize that all hospitalized COVID-19 patients are at high risk for VTE. Therefore, the standard of care is to provide prophylactic anticoagulation for all hospitalized COVID-19 patients irrespective of other traditional risks for VTE.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%
“…This may be reflected particularly in those admitted to the ICU, where the reported incidence of primarily venous thrombotic complications ranges from 31% to 69% among COVID-19 patients. 3,24,25 A small retrospective study of 49 mechanically ventilated patients from Belgium reported that the use of high-intensity thromboprophylaxis was associated with a lower occurrence of PE. 26 Similarly, a Swedish study of 152 patients demonstrated reduced incidence of thromboembolic events and mortality in those receiving high-dose chemoprophylaxis versus "medium" or "low" (high 13.5% versus medium 25% versus low 38.8%; P = 0.02).…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%